Analisis Pengaruh Disiplin, Stress dan Motivasi Terhadap Kinerja Karyawan dan Dampaknya Pada Produktivitas Kerja - Medinal - -; Hadiyanto - Budisetio; Wargianto - - (Universitas PGRI Palembang, 2017)
This study takes an object on Consecrated Bakti Timah Hospital at Pangkalpinang. Reasons for the selection of objects is due to some problems related to the low level of discipline , high stress levels, and employees are less motivated to work better, so that the performance decreases, which in turn have an impact on labor productivity in the company. The purpose of this study was to determine the effect of discipline, stress and work motivation on employee performance and the impact on productivity in Bakti Timah Hospital at Pangkalpinang. The research sample of 190 respondents. Sampling was done by proportional random sampling technique, where the population is divided into groups, namely: medical groups, medical groups care, non-medical care group, and non-medical groups. While the sample collection technique using the formula of Taro Yamane or Slovin. Data analysis tools are used path analysis. The results of research that together have a significant contribution, the effect of variable magnitude discipline ( X1 ) Stress ( X2 ) and Motivation ( X3 ) simultaneously on performance ( Y ) of 55.1 %. As well as the influences of the coefficient of determination expressed by the amount of Performance ( Y ) to the variable productivity of 65.3 %.Keywords : Thesis, Effect of Discipline, Stress, Motivation, Performance, and Productivity, and Simultaneous Partial Hospital Bakti Timah Pangkalpinang.